Sialoblastoma- long-term follow-up and remission for a rare salivary malignancy - Linda Granowetter; Margaret Brandwein-Gensler; Rachel Kessel; Kanwal Majeed Farooqi; Deepa Manwani (Rare Tumors, 2011)
Sialoblastoma is a rare salivary neoplasm which presents either congenitally or during early infancy. It was originally considered a benign neoplasm, however a number of reported cases have documented locoregional recurrence and distant metastases. Currently, there is no consensus on the appropriate treatment for this neoplasm. We report on long term follow-up of a patient with metastatic sialoblastoma, and a brief discussion of the possible treatment modalities currently being considered.